2010
DOI: 10.1158/0008-5472.can-10-0202
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor-1 Signaling Promotes Mobilization of Macrophage Lineage Cells from Bone Marrow and Stimulates Solid Tumor Growth

Abstract: Vascular endothelial growth factor and its receptors, including Flt-1 and Flk-1, are involved in angiogenesis under physiologic and pathologic conditions. Recently, Flt-1-expressing cells were reported to contribute to the intracranial growth of glioma cells. However, the role of Flt-1 signaling in solid tumor growth in s.c. tissue has not been elucidated. To investigate how Flt-1 signaling is involved in the proliferation of solid tumors, we implanted tumor cells into wild-type (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 45 publications
3
65
0
1
Order By: Relevance
“…Preclinical tumor xenografts have been used to define many of the mechanisms with the potential to influence response to VEGFi, other angiogenic factors (7), bone marrow-derived cells (5,6), or by recruitment of stromal fibroblasts/pericytes into the tumor which drive the maturation of tumor vessels (8)(9)(10). Our analysis suggests that those mechanisms of resistance defined in preclinical tumor xenografts may be most relevant to those diseases that display a tumor vessel phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Preclinical tumor xenografts have been used to define many of the mechanisms with the potential to influence response to VEGFi, other angiogenic factors (7), bone marrow-derived cells (5,6), or by recruitment of stromal fibroblasts/pericytes into the tumor which drive the maturation of tumor vessels (8)(9)(10). Our analysis suggests that those mechanisms of resistance defined in preclinical tumor xenografts may be most relevant to those diseases that display a tumor vessel phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Additional studies in preclinical models have revealed a number of putative mechanisms that may contribute to both intrinsic and acquired VEGFi resistance. One of the first mechanisms proposed as mediating resistance to VEGF-A neutralization was the presence or recruitment of inflammatory infiltrate, specifically CD11b, GR-1-positive cells derived from the bone marrow, in response to upregulation of tumor-derived factors (5,6). A complementary resistance mechanism is the expression of factors that drive alternative angiogenic pathways such as high expression of the potent angiogenic stimulus FGF-2 (7).…”
Section: Introductionmentioning
confidence: 99%
“…To complicate matters further, divergent tumor growth phenotypes have been reported when implanting tumors in a tyrosine kinase-dead FLT1 mutant mouse model, with some studies reporting a reduction in tumor growth/metastasis (Hiratsuka et al 2001(Hiratsuka et al , 2002Kerber et al 2008; Van de Veire et al 2010;Schmidt et al 2011) and others showing no effect (Dawson et al 2009;Bais et al 2010;Muramatsu et al 2010). Presumably, the importance of PlGF/ FLT1 is context-dependent.…”
Section: Plgf: a Multitasking Disease-restricted Cytokinementioning
confidence: 99%
“…A different population of VEGFR-1-expressing cells, circulating VEGFR-1-expressing hematopoietic cells, has recently been implicated in tumor growth and progression (12)(13)(14)(15). To exclude the possibility that we are in fact studying VEGFR-1-expressing hematopoietic cells, control experiments were done using pan-hematopoietic cell marker CD45.…”
Section: Chemotherapy Enhances Vegfr-1 Expression On Ecs In Vivomentioning
confidence: 99%